The Kyoto Protocol's Clean Development Mechanism: Prospects for Japan-Philippines Partnership - Palanca-Tan, Rosalina (Archīum Ateneo, 2006)
The Kyoto Protocol's Clean Development Mechanism (CDM) is a system by which a developed country can earn carbon emission reduction (ER) credits through an emission-mitigating project undertaken in a developing country. While allowing developed countries to meet their Kyoto Protocol commitments at less cost, CDM benefits the host developing countries with new capital investments and the transfer of clean technologies. In view of the potential supply of ERs on the Philippine side and a pressing demand on Japan's side, this article explores the relatively low level of CDM cooperation between the Philippines and Japan, and suggests ways of moving forward.